2015
DOI: 10.5455/ijmsph.2015.01052015354
|View full text |Cite
|
Sign up to set email alerts
|

Audit of sepsis in neonatal surgeries at tertiary-care level hospital in India

Abstract: Background: Postoperative sepsis, which has high morbidity and mortality, is a major problem affecting the outcome of neonatal surgeries. Adequate treatment and preventive measures for sepsis can decrease the morbidity and mortality in neonatal surgeries. Objective: (1) To study the incidence of sepsis in neonatal surgical patients and (2) To study the causative organisms and their sensitivity to antibiotics in such sepsis. Materials and Methods: A prospective, observational study was carried out in the tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…When compared to women at parity one, women at parity two were less likely to use LNB. This result is consistent with a previous study by Bhatt et al [ 35 ], which found that women who had more than one birth were less likely to use LNB. Alemu et al [ 36 ] found that parity level was substantially correlated with LNB practice, which corroborated the current conclusion.…”
Section: Discussionsupporting
confidence: 93%
“…When compared to women at parity one, women at parity two were less likely to use LNB. This result is consistent with a previous study by Bhatt et al [ 35 ], which found that women who had more than one birth were less likely to use LNB. Alemu et al [ 36 ] found that parity level was substantially correlated with LNB practice, which corroborated the current conclusion.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our study, other studies conducted found that out of 50 neonates were ventilated in the study, 6 similarly 6.83% of neonates required mechanical ventilation in another similar study. 7 In addition to this another study found 30.7% of neonates were ventilated, 8 and another study found 72 neonates required mechanical ventilation. 9 Our study has found that 52.32% of the mechanically ventilated newborn has underlying perinatal asphyxia however similar study found that RDS (58.9%) was the most common indication for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 79%
“…The most common diagnoses of the expired babies were Anorectal Malformation (ARM) and Gastroschisis; this might be due to the higher incidence of these anomalies in this region. Reports from other institutes of Bangladesh and India reflect this fact (7,8,15). The highest percentage of babies died with Gastroschisis and Esophageal atresia.…”
Section: Discussionmentioning
confidence: 93%